Math, asked by PriteshBang, 1 year ago

if x/b+c-a=y/c+a-b=z/a+b-c then (b-c)x+(c-a)y+(a-b)z is​


anshu4395: No
PriteshBang: ok
PriteshBang: u have a bf..???
anshu4395: No
PriteshBang: r u use wp
anshu4395: Whi to banana h
PriteshBang: can we chat on sms..??
PriteshBang: what's happen..???
PriteshBang: hey want to !!x chat me..???
PriteshBang: hi

Answers

Answered by brunoconti
19

Answer:

Step-by-step explanation:

BRAINLIEST BRAINLIEST BRAINLIEST BRAINLIEST BRAINLIEST BRAINLIEST BRAINLIEST BRAINLIEST BRAINLIEST BRAINLIEST BRAINLIEST BRAINLIEST

Attachments:

PriteshBang: Thanks....(◕‿◕)
Answered by brindabkundu
2

Answer: 0

Step-by-step explanation:

Let x/b+c-a = y/c+a-b = z/a+b-c = k ......(1)

x/b+c-a = k

:. x=k(b+c-a) .................(2)

y/c+a-b = k

:. y=k(c+a-b) .................(3)

z/a+b-c = k

:. z=k(a+b-c) ..................(4)

Now from (1), (2), (3) &(4) ,

(b-c)x+(c-a)y+(a-b)z

= [(b-c)(b+c-a)+(c-a)(c+a-b)+(a-b)(a+b-c)]k

= [b(b+c-a)-c(b+c-a)+c(c+a-b)-a(c+a- b)+a(a+b-c)-b(a+b-c)]k

= (b^2+bc-ab-bc-c^2+ac+c^2+ac-bc-ac

-a^2+ab+a^2+ab-ac-ab-b^2+bc)k

= (0)k

= 0

Similar questions